1989
DOI: 10.2105/ajph.79.2.216
|View full text |Cite
|
Sign up to set email alerts
|

The sociologic context of occupational health in South Africa.

Abstract: Introduction This paper seeks to present an account of the occupational health situation in South Africa. Part I is an historical documentation of the evolution of the occupational health system, covering both political and legislative aspects up until the early 1970s, which mark a political and social transition in the society; Part II consists ofa demographic and sociologic profile of the society in relation to occupational health; Part III deals with the relatively underdeveloped occupational health infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The practice of OHS in South Africa has always had a political aspect to it, but that politics has largely been one confined to worker-employer-state interactions. [40][41][42][43] Moving out of the world of formal employment takes OHS into a different politics-the politics of informality. Power relations play out here at several levels, as the reflections revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of OHS in South Africa has always had a political aspect to it, but that politics has largely been one confined to worker-employer-state interactions. [40][41][42][43] Moving out of the world of formal employment takes OHS into a different politics-the politics of informality. Power relations play out here at several levels, as the reflections revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Within the African setting, work-related health and noncommunicable diseases have received little attention (Boutayeb & Boutayeb, 2005;Delamothe, 2009;Jeebhay & Jacobs, 1999, Chap. 19;Myers & Macon, 1989;Unwin et al 2001), with recent exceptions of diabetes, hypertension and cardiovascular diseases. It is for this reason that the nurse-in-charge in Tsilitwa reported that focus was on "fashionable diseases such as AIDS", a statement which captures the tendency to emphasise a particular disease at a given period to the neglect of others.…”
Section: Discussionmentioning
confidence: 99%
“…Other challenges facing a future South Africa include occupational and psycho-social diseases associated with industry (Zwi, Fonn and Steinberg, 1988). Black workers are subjected to numerous toxic substances from asbestos to pesticides (WHO, 1983: 194-204;Myers, 1987;Packard, 1989b;Durning, 1990: 18-20). Indeed, one open question is whether exposure to mutagenic pesticides is associated with high rates of congenital deformities and high peri-natal mortality (WHO, 1983: 107).…”
Section: Health Statusmentioning
confidence: 99%